2020
DOI: 10.1093/brain/awaa325
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological subtypes of Alzheimer’s disease based on cerebrospinal fluid proteomics

Abstract: Using CSF proteomics, Tijms et al . identify three Alzheimer’s disease subtypes that show: 1) hyperplasticity and increased BACE1 levels; 2) innate immune activation; and 3) blood-brain barrier dysfunction with low BACE1 levels. Future therapeutics may need tailoring to individual disease subtypes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
132
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 84 publications
12
132
0
Order By: Relevance
“…Higginbotham et al summarized the CSF DE proteins into synaptic, vascular, myelin, immunological, and metabolic panels, and applied the five biomarker panels to the classification of asymptomatic AD subjects into two subgroups [ 75 ]. In agreement with the heterogeneity of AD-related cases, three molecular subtypes are implicated by transcriptomics [ 200 ] and CSF proteomics [ 134 ].…”
Section: Proteomics-based Biomarker Discovery In Admentioning
confidence: 69%
“…Higginbotham et al summarized the CSF DE proteins into synaptic, vascular, myelin, immunological, and metabolic panels, and applied the five biomarker panels to the classification of asymptomatic AD subjects into two subgroups [ 75 ]. In agreement with the heterogeneity of AD-related cases, three molecular subtypes are implicated by transcriptomics [ 200 ] and CSF proteomics [ 134 ].…”
Section: Proteomics-based Biomarker Discovery In Admentioning
confidence: 69%
“…8 In line with this recognition, more recent findings suggest that cerebrospinal fluid proteomics may define subtypes of AD that are potentially relevant from a pathophysiological perspective. 9 The same may By contrasting the results of a traditional frequentist meta-analysis with the results from a Bayesian meta-analysis, and showing how an additional trial result would change the overall results of the latter meta-analysis, we illustrate that further pursuing AAB immunotherapy as treatment for AD as a rather homogeneous condition is likely futile.…”
Section: Discussionmentioning
confidence: 94%
“…For ADNI biomarker abnormality was defined by Aβ42 levels <192 pg/mL and t-tau levels >93 pg/mL [18,23,24]. In EMIF-AD MBD cut-offs for p were study specific as previously reported [17,18,23,24]. Cluster analyses were performed on proteomic data performed using tandem mass tag (TMT) technique with 10 + 1 plexing in EMIF-AD MBD using high-pH reverse phase HPLC for peptide prefractionation [17,25,26].…”
Section: Cerebrospinal Fluid Datamentioning
confidence: 99%
“…In EMIF-AD MBD cut-offs for p were study specific as previously reported [17,18,23,24]. Cluster analyses were performed on proteomic data performed using tandem mass tag (TMT) technique with 10 + 1 plexing in EMIF-AD MBD using high-pH reverse phase HPLC for peptide prefractionation [17,25,26]. The EMIF-AD MBD mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE [27] partner repository with the dataset identifier PXD019910 and 10.6019/PXD019910.…”
Section: Cerebrospinal Fluid Datamentioning
confidence: 99%
See 1 more Smart Citation